Electron Impact Studies on the N-formylderivative of Ethyl Cyano-2-o-aminophenylhydrazono Acetate - Prasad, J.; Singh, S.N. (Asian Journal of Chemistry, 2016)
Mass spectral studies on the N-formylderivative of ethyl cyano-2-o-aminophenylhydrazono acetate have been carried out and their fragmentation patterns have been rationalised. None of the products shows the ion of highest abundance, i.e., the base peak as the molecular ion. The base peak is at m/e 107.